2012
DOI: 10.4314/wsa.v38i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Swimming pools and intra-city climates: Influences on residential water consumption in Cape Town

Abstract: Water demand management can be effective as a resource management approach if demand estimation is accurate and consumption determinants are defined. While determinants such as household income, regional climate, water price, property size and household occupancy have been comprehensively studied and modelled, other determinants such as swimming pools and intra-city climates have not. This study examines residential water consumption in the City of Cape Town in 2008/2009, under property size regimes, to separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…When all property areas are lumped together, the impact of a swimming pool is an average increase of 8.2 kℓ/month or 30% -which is similar to that reported by Siebrits (2012). However, the significant differences between the various bands suggest that other factors are impacting the water demand, apart from -but linked to -the swimming pool.…”
Section: Roof Areasupporting
confidence: 71%
“…When all property areas are lumped together, the impact of a swimming pool is an average increase of 8.2 kℓ/month or 30% -which is similar to that reported by Siebrits (2012). However, the significant differences between the various bands suggest that other factors are impacting the water demand, apart from -but linked to -the swimming pool.…”
Section: Roof Areasupporting
confidence: 71%
“…Studies confirm that the main variables that determine residential water use are household income, property/stand size, property price, number of occupants in a dwelling or household, as well as the cost of water (Duke et al 2002;van Zyl et al 2007;Siebrits 2012). The informal settlement of Dunoon was initially selected as one of the 11 suburbs, however, on further investigation it was determined that there was no discrete bulk water meter data to accurately represent the informal service delivery in this settlement, with the only available data being for formal houses, businesses and industries.…”
Section: Socio-economic Clusteringmentioning
confidence: 99%
“…Studies have confirmed that an integrated approach that makes use of incentives and communication, together with regulatory measures, is more effective in encouraging water conservation practices than tariffs and restrictions alone (Renwick & Archibald 1998;Savenjie & van der Zaag 2002;Siebrits 2012). For example, water restrictions and rationing are effective in reducing demand, but result in a need for cost recovery following a crisis, and consequently increasing the water rates for all water users regardless of their behaviour during the drought (Duke et al 2002).…”
Section: Non-priced-based Wdm Strategiesmentioning
confidence: 99%
See 2 more Smart Citations